Challenges and Limitations of Terahertz Phase Imaging Method - Kaluza, Mateusz; Nieradka, Adrianna; Komorowski, Paweł; Siemion, Agnieszka (Photonics Letters of Poland, 2024)
Advancements in terahertz (THz) technology have significantly enhanced imaging systems, while improving imaging contrast remains critical, especially for transparent objects. This study presents a 4f imaging system using the positive phase contrast method, tested on a transparent 3D-printed object with varying phase retardations. Parasitic effects observed during experiments highlight key challenges in THz imaging, enabling the identification of solutions to improve system performance and enhance image quality. Full Text: PDF References D.M. Mittleman, "Twenty years of terahertz imaging", Opt. Express 26, 8 (2018). CrossRef Z. Yan, L.G. Zhu, K. Meng, W. Huang, and Q. Shi, "THz medical imaging: from in vitro to in vivo", Trends Biotechnol. 40, 7 (2022). CrossRef G.M. Png et al., "The impact of hydration changes in fresh bio-tissue on THz spectroscopic measurements", Phys. Med. Biol. 53, 13 (2008). CrossRef L. Wang, "Terahertz Imaging for Breast Cancer Detection", Sensors 21, 19 (2021). CrossRef Y. Peng, C. Shi, X. Wu, Y. Zhu, and S. Zhuang, "Terahertz Imaging and Spectroscopy in Cancer Diagnostics: A Technical Review", BME Front. 2020, (2020). CrossRef Y. Tzydynzhapov et al., "New Real-Time Sub-Terahertz Security Body Scanner", J. Infrared Millim. Terahertz Waves 41, 6 (2020). CrossRef A.G. Davies, et al., "Terahertz spectroscopy of explosives and drugs", Mater. Today 11, 3 (2008). CrossRef S. Zhong, "Progress in terahertz nondestructive testing: A review", Front. Mech. Eng. 14, 3 (2019). CrossRef S. Fan et al., "Terahertz non-destructive imaging of cracks and cracking in structures of cement-based materials", AIP Adv. 7, 11 (2017). CrossRef T. Löffler et al., "Terahertz dark-field imaging of biomedical tissue", Opt. Express 9, 12 (2001). CrossRef G. Valušis, A. Lisauskas, H. Yuan, W. Knap, and H.G. Roskos, "Roadmap of Terahertz Imaging 2021", Sensors 21, 12 (2021). CrossRef F. Zernike, "The Phase-Contrast Method in Microscopic Observation", Z Tech Physik 16, 454 (1935). CrossRef I. Mehdi, J.V. Siles, C. Lee, and E. Schlecht, "THz Diode Technology: Status, Prospects, and Applications", Proc. IEEE 105, 6 (2017). CrossRef M. Kaluza, M. Walczakowski, and A. Siemion, "Exploring the Impact of 3D Printing Parameters on the THz Optical Characteristics of COC Material", Materials 17, 20 (2024). CrossRef M. Sypek et al., "Highly efficient broadband double-sided Fresnel lens for THz range", Opt. Lett. 37, 12 (2012). CrossRef K. Zeranska-Chudek, A. Lapinska, A. Siemion, A.M. Jastrzębska, M. Zdrojek, "Terahertz time domain spectroscopy of graphene and MXene polymer composites", J. Appl. Polym. Sci. 138, 10 (2021). CrossRef A. Siemion, "Paraffin Diffractive Lens for Subterahertz Range—Simple and Cost Efficient Solution", IEEE Trans. Terahertz Sci. Technol. 11, 4 (2021). CrossRef